2003
DOI: 10.1038/sj.ijo.0802307
|View full text |Cite
|
Sign up to set email alerts
|

Lean, nondiabetic Asian Indians have decreased insulin sensitivity and insulin clearance, and raised leptin compared to Caucasians and Chinese subjects

Abstract: OBJECTIVE:To study and compare the insulin sensitivity of healthy, nondiabetic Asian Indians with that of two other ethnic groups (Caucasian and Chinese) living in Singapore. DESIGN: Study of insulin sensitivity using euglycaemic hyperinsulinaemic glucose clamp. SUBJECTS: A total of 10 healthy, lean, young male subjects of each ethnic group, matched for age, body mass index (BMI) and physical activity. They all had normal glucose tolerance and had no family history of diabetes. MEASUREMENTS: Anthropometric par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
57
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 35 publications
7
57
1
Order By: Relevance
“…Finally, other adipokines and inflammatory markers such as retinol binding protein-4, interleukin-6, leptin and resistin may contribute to ethnic differences in insulin resistance and were not measured in our study. 47 In summary, our results suggest that the higher degree of insulin resistance in Malays compared with Chinese was due to general adiposity. When Asian Indians were compared with Chinese, greater general adiposity, abdominal fat distribution, and higher CRP independent of adiposity appeared to contribute to the greater insulin resistance in Asian Indians.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Finally, other adipokines and inflammatory markers such as retinol binding protein-4, interleukin-6, leptin and resistin may contribute to ethnic differences in insulin resistance and were not measured in our study. 47 In summary, our results suggest that the higher degree of insulin resistance in Malays compared with Chinese was due to general adiposity. When Asian Indians were compared with Chinese, greater general adiposity, abdominal fat distribution, and higher CRP independent of adiposity appeared to contribute to the greater insulin resistance in Asian Indians.…”
Section: Discussionmentioning
confidence: 74%
“…46 More specifically, although culturally distinct, Malays in Singapore had a greater genetic similarity with Chinese than Asian Indians. 46,47 Greater general adiposity of Malays as compared with Chinese explained their greater insulin resistance in our study and targeting excess weight gain in Malays should have high priority in public health efforts for chronic disease prevention. 45 Compared with ordinary regression analysis, path analysis has the advantage that it allows examination of the potential causal processes underlying an observed relationship and to estimate the relative importance of alternative paths of influence in a complicated system.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the Indian patient with type 2 diabetes (T2D) tends to be diagnosed a decade earlier, is characterised by a lower body mass index (BMI) and is more centrally obese when compared with patients of Caucasian origin (3). Additionally, non-diabetic south Asians are more insulin resistant (4,5) and have an adverse fat distribution with more abdominal, hepatic and intramyocellular fat (6, 7) when compared with those from other ethnic groups with a similar BMI.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have repeatedly shown that South Asians have higher fasting insulin concentrations compared with other ethnic groups regardless of age, gender, or BMI, suggesting a higher rate of IR in this population (15,16,17,18,19,20,21,22,23,24,25). Already in South Asian neonates' the fasting insulin levels are markedly higher compared with European White Caucasian neonates' (26,27), and fasting insulin remains higher in school children (28,29) and teenagers (30).…”
Section: Introductionmentioning
confidence: 98%